The incidence of ventilator-associated pneumonia (VAP) in a tertiary-care center: Comparison between pre- and post-VAP prevention bundle - Sara Osman; Yousef M. Al Talhi; Mona AlDabbagh; Mohamed Baksh; Mohamed Osman; Maha Azzam (Journal of Infection and Public Health, 2020)
Introduction: Ventilator-associated pneumonia (VAP) is a nosocomial infection that develops 48 h after the initiation of mechanical ventilatory support. Current evidence-based guidelines demonstrate that VAP prevention is feasible through the implementation of certain VAP prevention bundle of interventions simultaneously. We aimed in this study to investigate the effect of VAP prevention pre- and post- implementation. Methods: This is a single-center, cohort study that took place at the Pediatric Intensive Care Unit (PICU) of King Abdulaziz Medical City (KAMC), Jeddah, Saudi Arabia from January 2015 to March 2018 and assessed the rate of VAP before and after implementation of the bundle. Results: The study included 141 children, 95 were included from the pre-bundle group and 36 from the bundle group. VAP developed in 35% of the pre-bundle group compared to 31% of the bundle group (p = 0.651) with incidence rates equaled to 18 and 12 per 1000 ventilator days, respectively. Conclusion: This study found that VAP bundle did not significantly reduce VAP rate in the PICU. Further large prospective multi-center studies with longer intervention duration are indicated to investigate the benefits of using VAP prevention bundle. Keywords: Ventilator-associated pneumonia, VAP, VAP Bundle, PICU